Influence of Fibroblasts on Mammary Gland Development, Breast Cancer Microenvironment Remodeling, and Cancer Cell Dissemination - Avagliano, Angelica (Cancers (Basel), 2020)
The stromal microenvironment regulates mammary gland development and tumorigenesis. In normal mammary glands, the stromal microenvironment encompasses the ducts and contains fibroblasts, the main regulators of branching morphogenesis. Understanding the way fibroblast signaling pathways regulate mammary gland development may offer insights into the mechanisms of breast cancer (BC) biology. In fact, the unregulated mammary fibroblast signaling pathways, associated with alterations in extracellular matrix (ECM) remodeling and branching morphogenesis, drive breast cancer microenvironment (BCM) remodeling and cancer growth. The BCM comprises a very heterogeneous tissue containing non-cancer stromal cells, namely, breast cancer-associated fibroblasts (BCAFs), which represent most of the tumor mass. Moreover, the different components of the BCM highly interact with cancer cells, thereby generating a tightly intertwined network. In particular, BC cells activate recruited normal fibroblasts in BCAFs, which, in turn, promote BCM remodeling and metastasis. Thus, comparing the roles of normal fibroblasts and BCAFs in the physiological and metastatic processes, could provide a deeper understanding of the signaling pathways regulating BC dissemination. Here, we review the latest literature describing the structure of the mammary gland and the BCM and summarize the influence of epithelial-mesenchymal transition (EpMT) and autophagy in BC dissemination. Finally, we discuss the roles of fibroblasts and BCAFs in mammary gland development and BCM remodeling, respectively.